2021
DOI: 10.1093/bjsopen/zrab085
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair of diastasis recti abdominis provides long-term improvement of abdominal core function and quality of life: a 3-year follow-up

Abstract: Background Diastasis recti abdominis (DRA) is a condition affecting many post-partum women. The aim of this study was to evaluate long-term results of surgical repair of DRA in a cohort of post-partum women. Methods Sixty post-partum women with DRA and training-resistant core dysfunctions were included. Surgical repair was performed with suture plication of the linea alba. Abdominal core function was evaluated with the abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
8
0
1
Order By: Relevance
“…It has to be noted, that in many individuals, there is a laxity of the linea alba and the anterior abdominal wall myofascial complexes, which clinically can manifestate as a "bulge" during Valsalva's maneuver between the recti muscles in the epigastric region and not surpisingly DOI: http://dx.doi.org/10.5772/intechopen.102734 can be mistaken as a ventral hernia. This condition, in which only laxity of the linea alba exists without the presence of a defined, true anatomical defect exists, is called deverication of recti and its operative managment is completely different of a typical ventral hernia [15]. Therefore, the operating surgeon should have a low threshold for assesing these patients with a further imaging modality (ie ultasound, compute tomography or dynamic magnetic resonance scans) to confidently differentiate between the two conditions.…”
Section: Types Of Ventral Herniasmentioning
confidence: 99%
“…It has to be noted, that in many individuals, there is a laxity of the linea alba and the anterior abdominal wall myofascial complexes, which clinically can manifestate as a "bulge" during Valsalva's maneuver between the recti muscles in the epigastric region and not surpisingly DOI: http://dx.doi.org/10.5772/intechopen.102734 can be mistaken as a ventral hernia. This condition, in which only laxity of the linea alba exists without the presence of a defined, true anatomical defect exists, is called deverication of recti and its operative managment is completely different of a typical ventral hernia [15]. Therefore, the operating surgeon should have a low threshold for assesing these patients with a further imaging modality (ie ultasound, compute tomography or dynamic magnetic resonance scans) to confidently differentiate between the two conditions.…”
Section: Types Of Ventral Herniasmentioning
confidence: 99%
“…При анализе результатов лечения ДПМЖ A. Olsson et al (2021) выявлено снижение выраженности симптомов недержания мочи после операции, что указывает на связь между восстановлением топографоанатомических соотношений передней брюшной стенки и стабилизацией мышц тазового дна [46].…”
Section: таблицаunclassified
“…A few months after surgery a skin fold is reduced due to scar remodelling and surgical correction of skin excess postponed to that time allows to avoid over-or under-treatment [29]. Olsson et al [30] reported no recurrences after suture plication of the linea alba and functional improvement of this surgical reconstruction persisted for 3 years. Authors describe recurrences after open plication or laxity of the abdominal wall with protrusion of linea alba, what should be interpret as recurrent DRA [3].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Although cosmetic result of a surgical intervention is of high importance, it is not yet evaluated which surgical technique has the most satisfying cosmetic outcome [3,13,30,41]. To date, despite the importance of cosmetic results, the majority (85%) of published cases are open ones [3].…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation